1980
DOI: 10.1002/neu.480110109
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of an octopaminergic neuron and its terminals

Abstract: The large octopaminergic dorsal unpaired median neuron of the locust that innervates the extensor tibiae muscle, DUMETi, was examined electronmicroscopically. Its soma contains many Golgi complexes apparently making dense-core vesicles similar to those found in peripheral branches and terminals. There are also larger stores of the dense material in the soma, especially near the exit of the principal neurite, that are not in vesicular form. Since the neurons can be penetrated and stimulated by microelectrodes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(37 citation statements)
references
References 25 publications
1
35
1
Order By: Relevance
“…It is not known definitively whether T␤M is expressed in similar vesicles of the invertebrate nervous system. Octopamine, however, is associated with dense core vesicles of dorsal unpaired median neurons in locusts (29,30), and studies also have shown that T␤M is localized in octopaminergic neurons/cell bodies (of honeybees and lobster) (8,9,31). A recent study demonstrated that octopamine-containing cells of the Drosophila reproductive system, including vesicles of the ovarian sheath, were immunoreactive for T␤M.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known definitively whether T␤M is expressed in similar vesicles of the invertebrate nervous system. Octopamine, however, is associated with dense core vesicles of dorsal unpaired median neurons in locusts (29,30), and studies also have shown that T␤M is localized in octopaminergic neurons/cell bodies (of honeybees and lobster) (8,9,31). A recent study demonstrated that octopamine-containing cells of the Drosophila reproductive system, including vesicles of the ovarian sheath, were immunoreactive for T␤M.…”
Section: Discussionmentioning
confidence: 99%
“…At the ultrastractural level, dendritic neuronal processes in the central nervous system and peripheral neuromuscular terminals of the UM neurons appear to contain large dense-core vesicles, together with less numerous, small clear vesicles. However, dense-core vesicles, which are thought to contain octopamine, were never found in typical presynaptic specializations, suggesting that octopamine may be released nonsynaptically (Oertal et al, 1975;Hoyle et al, 1980;Kiss et al, 1984;Watson, 1984;Atwood et al, 1993;Rheuben, 1995;Pflü ger and Watson, 1995).…”
mentioning
confidence: 93%
“…Octopamine regulates hormone release in cockroaches (Downer et al, 1984), induces lipid and carbohydrate metabolism in crickets (Fields and Woodring, 1991), and modulates feeding behavior of blowflies (Long and Murdock, 1983) and bees (Bicker and Menzel, 1989;Braun and Bicker, 1992). Additionally, both somatic and visceral muscles are innervated by octopaminecontaining endings in several insect species (see, e.g., Hoyle et al, 1980). Physiological studies indicate that octopamine has excitatory modulatory actions at these muscles (Hoyle, 1984;Hidoh and Fukami, 1987;Malamud et al, 1988).…”
mentioning
confidence: 99%